The optimization management of the goal throws from the extremes in handball game, junior players i (girl's) - Cicma, I. T. (Science, Movement & Health, 2015)
Aim. The paper objective consists of showing that a good management leads to an optimization of the goal throws efficiency for the junior I handball players, from the outside left and right positions. Methods. In order to elaborate and carry the thesis into effect, we used the experimental method, the tests method, the mathematical method of statistics, and the graphical method. Results. On the score of the implemented intercession, the one used within the experiment, we could notice an increase of the medium efficacy of the goal throws on the outside position, from 9.5 throws to 13.5 throws, as well as an individual progress of each player, between 3 and 5 throws. Conclusions. As a general conclusion, we can affirm that the thesis` aim has been accomplished. The experiment clearly showed us that implementing and applying a good management we can obtain an optimization or the goal throws from the outside.